Correction: Effects of Low-Intensity Pulsed Ultrasound on New Trabecular Bone during Bone-Tendon Junction Healing in a Rabbit Model: A Synchrotron Radiation Micro-CT Study. - Hongbin Lu (PLoS ONE, 2019)
[This corrects the article DOI: 10.1371/journal.pone.0124724.].